2003
DOI: 10.1089/153623003322234740
|View full text |Cite
|
Sign up to set email alerts
|

UP1 Extends Life of Primary Porcine Fetal Fibroblasts in Culture

Abstract: Genetic modification of somatic cell nuclei and subsequent nuclear transfer has opened an opportunity to create gene-targeted animals. However, somatic cells have a limited life span in culture and it is not possible to introduce precise genetic changes in both alleles in this narrow time window. To increase the life span of somatic cell in culture, both genetic and chemical approaches have been tried with varying success. Here, we report the effect of two anti-oxidants, glutathione and n-t-butyl hydroxylamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Porcine EG cells may be more amenable to reprogramming after reconstruction than differentiated somatic cells. Furthermore, the chromosomal stability of porcine EG cells, as previously reported (Shim et al, 1997), may yield consistent results in NT compared with somatic cells, such as fetal fibroblasts, that often exhibit chromosomal abnormalities in long-term culture (Mir et al, 2003). Successful acceptance of xenografts occurs after overcoming a series of obstacles, including hyperacute, acute vascular, cellular, and chronic rejection (Khalpey et al, 2004;Yang & Sykes, 2007).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Porcine EG cells may be more amenable to reprogramming after reconstruction than differentiated somatic cells. Furthermore, the chromosomal stability of porcine EG cells, as previously reported (Shim et al, 1997), may yield consistent results in NT compared with somatic cells, such as fetal fibroblasts, that often exhibit chromosomal abnormalities in long-term culture (Mir et al, 2003). Successful acceptance of xenografts occurs after overcoming a series of obstacles, including hyperacute, acute vascular, cellular, and chronic rejection (Khalpey et al, 2004;Yang & Sykes, 2007).…”
Section: Discussionsupporting
confidence: 56%
“…Porcine EG cells may be more amenable to reprogramming after reconstruction than differentiated somatic cells. Furthermore, the chromosomal stability of porcine EG cells, as previously reported (Shim et al ., 1997), may yield consistent results in NT compared with somatic cells, such as fetal fibroblasts, that often exhibit chromosomal abnormalities in long-term culture (Mir et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the use of antioxidants did not result in any prolongation of the life span, however, Up1 expression increased the life span significantly. Thus, expression of Up1 may be useful in extending the life span of somatic cells in culture [35]. Therefore, Up1 down-regulation found in this study may contribute to the apoptosis as well as the growth inhibition of glioma cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 67%
“…UP1 has been shown to bind to DNA carrying single-stranded telomeric extensions at the 3' terminus and protects telomeric sequences against degradation by endo-and exonucleases (Dallaire et al, 2000). Furthermore, recent studies have demonstrated that overexpression of UP1 extends life of primary porcine fetal fibroblasts in culture by preventing telomere shortening (Mir et al, 2003). Thus, it is tempting to speculate that UP1 becomes methylated upon proliferating stimuli in a regenerating liver.…”
Section: Discussionmentioning
confidence: 99%